An Effort to Disengage Mind-Wandering (The Integrated Study between Psychology and Sufism) - Dwi Nugraini, Erna; Nurul Hikmah Sofyan (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
There are many factors that can eliminate someone’s focus, one of them is mind-wandering. It is a condition in which thoughts do not remain focused on the task at hand but range widely and spontaneously across other topics. It becomes a problem when the task requires full concentration, such as when a doctor performs a surgery, a scientist conducts an experiment, or a businessman presents a project plan in front of client. The study aims to offer alternative solution to disengage mind-wandering related to individual productivity by integrating theories from two disciplines. They are the theory of mindfulness in psychology, and the theory of waqt and ridha in Sufism. The method of this study is qualitative with a kind of library research. The data collection technique is a documentary. Data analysis techniques consist of hermeneutic and irfani method. The result of this study shows that by awareness of waqt, ridha, and mindfulness, an individual will give full attention to the task at one time by doing the best he can regardless of the desired or unwilling task and accepting all the thoughts, emotions, and bodily sensations that come from the experience without any effort to change it.